Missing Voices: Profile, Extent, and 12-Month Outcomes of Nonfatal Traumatic Brain Injury in Aboriginal and Non-Aboriginal Adults in Western Australia Using Linked Administrative Records. Issue 6 (November 2018) - Katzenellenbogen, Judith M.; Atkins, Emily; Thompson, Sandra C.; Hersh, Deborah; Coffin, Juli; Flicker, Leon; Hayward, Colleen; Ciccone, Natalie; Woods, Deborah; Greenland, Melanie E.; McAllister, Meaghan; Armstrong, Elizabeth M.
Abstract : Objective: To investigate differences in the profile and outcomes between Aboriginal and non-Aboriginal Western Australians (WAs) hospitalized with traumatic brain injury (TBI). Setting: WA hospitals. Participants: TBI cases aged 15 to 79 years surviving their first admission during 2002-2011. Design: Patients identified from diagnostic codes and followed up for 12 months or more using WA-wide person-based linked hospital and mortality data. Main Measures: Demographic profile, 5-year comorbidity history, injury mechanism, injury severity, 12-month readmission, and mortality risks. Determinants of 12-month readmission. Results: Of 16 601 TBI survivors, 14% were Aboriginal. Aboriginal patients were more likely to be female, live remotely, and have comorbidities. The mechanism of injury was an assault in 57% of Aboriginal patients (vs 20%) and transport in 33% of non-Aboriginal patients (vs 17%), varying by remoteness. One in 10 Aboriginal TBI patients discharged themselves against medical advice. Crude 12-month readmission but not mortality risk was significantly higher in Aboriginal patients (48% vs 36%). The effect of age, sex, and injury mechanism on 12-month readmission was different for Aboriginal and non-Aboriginal patients. Conclusion: These findings suggest an urgent need for multisectoral primary prevention of TBI, as well as culturally secure and logistically appropriate medical and rehabilitation service delivery models to optimize outcomes. Abstract : Supplemental Digital Content is Available in the Text.